Trail log - 2016 - Rolston, Holmes, 1932-2025, author (Colorado State University. Libraries, 2016)
Local hikes; March, Yellowstone wolf week; May-June, Taiwan, speaking, and local environmental trips and issues there, meeting with Chen Chien-Jen, vice-president of the country, Yehliu Geopark, Yang-Ming Shan National Park; June-July, Banff and Icefields Parkway, Canada; July, Virginia Beach, Virginia, First Landing State Park, sea kayaks and porpoises; September, Colorado Native Plant Society Conference, Boulder, Colorado, Jewel Mountain Habitat Conservation Area.